1993
DOI: 10.1007/bf00298717
|View full text |Cite
|
Sign up to set email alerts
|

Impact near the hip dominates fracture risk in elderly nursing home residents who fall

Abstract: Hip fractures among the elderly are a significant and rapidly growing public health problem. The prevailing view is that most hip fractures are the consequence of age-related bone loss or osteoporosis. However, because over 90% of hip fractures are the result of falls, we have undertaken a falls surveillance study to determine if factors related to the mechanics of falling are associated with increased risk of hip fracture. Case subjects with hip fracture and control subjects without hip fracture were sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
177
1
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(189 citation statements)
references
References 46 publications
8
177
1
3
Order By: Relevance
“…The fastest-growing segment of the population is people aged 80 and over, and this group has the highest hip fracture rate. Over 95 % of hip fractures are caused by falling [16], usually by falling sideways onto the hip [17] from a standing height. While it is possible that current rates will level off or even increase, it is also possible that rates will decline faster due to broad implementation of fall prevention strategies and/or improved screening and treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The fastest-growing segment of the population is people aged 80 and over, and this group has the highest hip fracture rate. Over 95 % of hip fractures are caused by falling [16], usually by falling sideways onto the hip [17] from a standing height. While it is possible that current rates will level off or even increase, it is also possible that rates will decline faster due to broad implementation of fall prevention strategies and/or improved screening and treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that oral bisphosphonates begin to reduce the risk of fractures within three to six months after they are started 37 . In addition to the initiation of medical treatment of osteoporosis, steps should be taken to prevent falls in the at-risk population, as nearly 80% of proximal humeral fractures and 90% of hip fractures are related to falls from a standing height 38,39 . A recent meta-analysis demonstrated the need for a multifaceted approach to the prevention of falls in hospitals and nursing homes and that no single intervention had a significant effect in a hospital setting the American Geriatrics Society, the British Geriatrics Society, and the American Academy of Orthopaedic Surgeons serve as a useful resource in the evaluation and prevention of falls in the geriatric population 41 .…”
Section: Discussionmentioning
confidence: 99%
“…This study may have several clinical implications for older adults with lateral instability and its relationship to lateral falls and hip fracture. Older adults tend to have decreased lower extremity muscle strength [34][35][36] and diminished lateral stability that may increase risks of lateral falls and hip fractures [37][38][39][40][41] . It is suggested that lateral body stability for crossing various obstacles is a good indicator of impaired balance in older adults 42) .…”
Section: Discussionmentioning
confidence: 99%